Організація партнерства викладачів і студентів у вищій освіті з метою якісного моніторингу - Осередчук Ольга; Olga Oseredchuk (II. Rákóczi Ferenc Kárpátaljai Magyar Főiskola, 2024)
Резюме. У статті виокремлено умови, при яких освітнє середовище у вищій школі здійснює соціалізуючий, виховний й освітній вплив на розвиток студентів, що можливо тільки при правильному моніторинговому підході до оцінки своєї діяльності. Розкрито успішні стратегії, зокрема, стратегію співробітництва й компромісу. Відмічено головні вміння, якими має володіти викладач у забезпеченні організації партнерства при здійсненні моніторингу вищої освіти. Показано переваги навчального діалогу студента зі студентом, викладача зі студентом; групових форм роботи; технологій проєктування при освітній діяльності, загалом і моніторинговій діяльності, зокрема. Виокремлено дослідницькі, творчі, інформаційні, розважальні, ігрові, практичноорієнтовані проєкти, що спрямовуються на здійснення якісного освітнього процесу і моніторингу вищої освіти, де необхідним є забезпечення організації партнерства викладачів і студентів.

Abstract. Monitoring the quality of professional training of future specialists in the Free Economic Zone on the basis of a partnership of teachers and students should be built for the needs of the educational institution, in particular, improving the quality of its activities. The conditions under which the educational environment in higher education has a socializing, educational and educational impact on student development, which is possible only with the right monitoring approach to assessing their activities and then contributes to the mastery of social, professional, personal experience. Describes the provision of external conditions of the educational process, favorable for subject-subject, partnership between teachers and students and the organization of an acceptable socio-psychological atmosphere, effective for educational and monitoring activities of students, which is a necessary factor for quality monitoring of higher education. The main skills that a teacher should have in ensuring the organization of partnership in the monitoring of higher education are noted: the ability to arouse the interest of each student and promote its development; the ability to reveal the creativity of the individual, creating partnership conditions for students that arouse their interest; ability to understand and explain the opinions of students that accompany their creative learning and creative activities. At the same time, we see the main task of the teacher in helping to form the unformed abilities of the student.
Ensuring the organization a partnership of teachers and students for the implementation of higher education quality monitoring
Keywords: організація партнерства; моніторинг якості вищої освіти; навчальний діалог; групові форми роботи; технології проєктування; проєкти; освітній процес